The Role of Digitalization in EAEU–ASEAN Dialogue - N. V. Fedorov (Сравнительная политика, 2024)
The article examines the role of digitalization in EAEU–ASEAN dialogue. The EAEU tries to develop cooperation with Southeast Asia, as for separate states, so with ASEAN. The sides have made some significant steps for strengthening of their interaction for the last years. However, the EAEU and ASEAN still have no free trade agreement or other formal document for economic cooperation. One of reasons for that seems to be relatively low level of trade ties and integration between EAEU and ASEAN member-states. EAEU and ASEAN officials make focus at their dialogue for facilitation and development of their economic cooperation. The digitalization takes important position in this interaction. The EAEU and ASEAN pay special attention to digitalization in their programs of development. The EAEU and ASEAN representatives accented the importance of digitalization as an instrument of cooperation (for example, in the relation of customs regulations and electronic trade). Digitalization issues have been included into agenda of different events with participation of the EAEU and ASEAN (for instance, Petersburg International Economic Forums). Representatives of the EAEU and ASEAN, separate member-states and business-communities discussed digitalization. Although the digitalization of EAEU–ASEAN cooperation makes the first steps, but, at the same time, we can see some practical results (on the example of activities of the Russia-Singapore Business Council and Singaporean company vCargoCloud). The digitalization in the framework of EAEU–ASEAN interaction has prospects for further development and can create conditions for strengthening ties between the EAEU and ASEAN.